2018
DOI: 10.22159/ajpcr.2017.v11i1.21839
|View full text |Cite
|
Sign up to set email alerts
|

Serovar Profile and Detection of Inva Virulence Gene Among Non-Typhoidal Salmonellae Serovars Isolated From Acute Gastroenteritis Cases in Coastal Karnataka, Southern India

Abstract: Objective: Non-typhoidal salmonellosis is one of the leading zoonosis in the world caused by non-typhoidal Salmonella (NTS). Invasive infections with NTS serovars occurs due to the presence of virulence genes like invA along with the immunosuppressive conditions of the patient. The study was conducted to isolate and identify the NTS serovars and their antimicrobial resistance profile from patients with diarrhea and also to detect the virulence marker -invA gene among these NTS serovars.Methods: A prospective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…Molecular detection of the most clinically relevant virulence genes and analysis of the associated virulence genotypes proved that the human ( n = 11) and poultry serovars ( n = 12) shared 11 genotypes. These findings are in agreement with those of a previous study [ 27 ] that reported that, out of 33 NTS, inv A was positive for 28 isolates, of which 89.3% patients were febrile. This study also revealed a positive correlation between the inv A gene and febrile illness, and therefore highlights the importance of inv A as an important marker for bloodstream invasion.…”
Section: Discussionsupporting
confidence: 93%
“…Molecular detection of the most clinically relevant virulence genes and analysis of the associated virulence genotypes proved that the human ( n = 11) and poultry serovars ( n = 12) shared 11 genotypes. These findings are in agreement with those of a previous study [ 27 ] that reported that, out of 33 NTS, inv A was positive for 28 isolates, of which 89.3% patients were febrile. This study also revealed a positive correlation between the inv A gene and febrile illness, and therefore highlights the importance of inv A as an important marker for bloodstream invasion.…”
Section: Discussionsupporting
confidence: 93%